The Impact of Wordlist Media in Learning Vocabulary - Febriyani; Mustain; Mariyatul Kiptiyah (Penerbit STKIP PGRI Bangkalan, 2021)
This research aimed to find out the Impact of Wordlist Media on Vocabulary Mastery for the students of Junior High School in Madura with the particular focus of finding new vocabularies in narrative text. This Quasi-Experimental research was implemented to examine. The Junior High School students in Madura using Wordlist Media. The results from this manipulation showed that the students through wordlist media were higher than those who were not using wordlist media. It proved that wordlist media was effective towards the students’ vocabulary mastery.